On Provinciality, Greed and Aspiration for a Metropolitan Life - Bagina, Elena (project baikal, 2017)
Provinciality is a painful feeling that causes uncertainty and dissatisfaction with oneself. In architecture, provinciality is manifested in a thoughtless imitation of the newest metropolitan trends, in distrust in local architects demonstrated by the authorities, as well as in incapability to appreciate the significance and identity of the non-metropolitan architecture. As a result, the province loses its valuable features, while the new architecture does not produce any masterpieces.